Publications: German economic research institutes on track - Rolf Ketzler; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2007)
The request for a strengthening of academic research at the German economic research institutes by the German Science Council more than a decade ago was founded on the crucial insight that sound policy advice the traditional task of the institutes can only be guaranteed in the long term if it is based on applied research carried out within the institutes themselves. Based on publications in academic journals, the central criterion of research evaluation, research output has improved remarkably in scope and quality and has involved an ever rising number of scholars within the institutes. It can be considered to be a substantial success of German reform policy, which should be internationally recognized. The present study demonstrates the implications of different methods of filtering and weighting research output to measure publication performance. The ranking of the institutes computed here on the basis of a wide range of alternative concepts provides fairly robust findings. The results are distorted, however, if they are based on a highly selective list of journals as was the case in previous literature.
Keywords: A11; 330; Economic research institutes; research evaluation; publication measurement; Wirtschaftsforschung; Wirtschaftsforschungsinstitut; Publikationsanalyse; Bewertung; Fachzeitschrift; Ranking-Verfahren; Deutschland